Single Phase Asymmetrical Cascaded MLI with Extreme Output Voltage Levels to Switch Ratio - Mahrous Ahmed; Essam Hendawi; Mohamed K. Metwaly (Institute of Advanced Engineering and Science, 2018)
This paper proposes an asymmetrical cascaded single phase H-bridge inverter. The proposed inverter consists of two modules with unequal and isolated dc sources. Each module is composed of dc source, conventional four switches H-bridge and single bidirectional switch. To increase the output voltage levels, the tertiary ratio, 1:3, between its two dc sources is adopted. Both the fundamental frequency and the multicarrier pulse width modulation (PWM) control schemes are employed to generate switches signals. By controlling the inverter modulation index, the proposed inverter can generate an output voltage having up to seventeen levels by using only two modules. The proposed topology has also the feature of modularity which means that it can be extended to any levels by adding new modules. The proposed topology is simulated using an inductive load and some selected simulation results have been provided to validate the proposed inverter.